Role of transvaginal sonography in various gynecological disorders - J. Mise, Pooja; Mise, Sangamesh J.; Mise, Aditya; Siddappa, Margol (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Transvaginal sonography (TVS) is a new diagnostic technique used for the evaluation of the female pelvis. The objective of the present study was to study the role of TVS and to assess the diagnostic accuracy in gynecological disorders. Methods: Total number of 100 patients attending OPDs with various complaints was selected by random technique of the study. All the patients have informed consent and thorough clinical examination including general, systemic and pelvic examination was conducted after taking a detailed history then the patients underwent TVS followed by one of the procedures like fractional curettage, dilatation and curettage and abdominal hysterectomy (with or without conservation of ovaries) or conservative management with regular follow up. Results: The sensitivity of TVS in diagnosing dysfunctional uterine bleeding (DUB) and pelvic inflammatory diseases (PID) was 100% and specificity was 85.1% and 95% respectively. For fibroids and ovarian mass diagnosis, sensitivity was 68.9% and 80.9% respectively and specificity was 100%. Diagnostic accuracy of clinical diagnosis was 70.0% whereas TVS had 94.0% of diagnostic accuracy in diagnosing various gynecological disorders. Conclusions: The final outcome is that TVS examination is an important non-invasive investigation, can be used as important diagnostic method in various gynecological disorders as it has got a high diagnostic accuracy.